Women's input and decision-making in agriculture are associated with diet quality in rural Tanzania - Madzorera, Isabel; Bliznashka, Lilia; Blakstad, Mia M.; Bellows, Alexandra L.; Canavan, Chelsey R.; Mosha, Dominic; Bromage, Sabri; Noor, Ramadhani; Webb, Patrick; Ghosh, Shibani; Kinabo, Joyce L.; Masanja, Honorati; et al. (Frontiers Media, 2023)
Background: Women’s empowerment is one critical pathway through which agriculture can impact women’s nutrition; however, empirical evidence is still limited. We evaluated the association of women’s participation, input, and decision-making in key agricultural and household activities with women’s diet quality. Methods: We analyzed data from a cross-sectional study of 870 women engaged in homestead agriculture. We used food frequency questionnaires to assess women’s diets and computed women’s diet quality using the Prime Diet Quality Score (PDQS) (range 0-42), which captures healthy and unhealthy foods. We evaluated women’s decision-making in 8 activities, food crop farming, cash crop farming, livestock raising, non-farm economic activities, wage/salary employment, fishing, major household expenditures and minor household expenditures. Generalized estimating equations (GEE) linear models were used to evaluate associations between (a) women’s participation, (b) decision-making, (c) adequate input, (d) adequate extent of independence in decision-making in agriculture, and (e) adequate input in use of agricultural income with their PDQS. Adequate input was defined as input into some, most or all decisions compared to input into few decisions or none. Adequate extent of independence was defined as input to a medium or high extent compared to input to a small extent or none. Findings: Median PDQS was 19 (IQR: 17-21). Women’s adequate input in decision-making on wage and salary employment (estimate: 4.19, 95% CI: 2.80, 5.57) and minor expenditures were associated with higher PDQS vs. inadequate input. Women with independence in decision-making on livestock production (estimate: 0.97, 95% CI: 0.05, 1.90) and minor household expenditures, and women with adequate decision-making in the use of income from wages/salaries (estimate: 3.16, 95% CI: 2.44, 3.87) had higher PDQS. Participation in agricultural activities was positively associated with PDQS. Conclusions: Women’s participation and input in decision-making in wage and salary employment, livestock production, and minor household expenditures were strongly associated with the consumption of better-quality diets. Women participating in multiple farm activities were also likely to have better diet quality. This study adds to the growing evidence on the pathways through which women’s empowerment may influence women’s nutrition in rural Tanzania.